STRATEGI KEPALA MADRASAH DALAM MENGIMPLEMENTASIKAN PROGRAM TAHFIDZUL QUR’AN DI MADRASAH ALIYAH NEGERI 1 SAMPANG DAN MADRASAH ALIYAH AL-ITTIHAD AL-ISLAMI CAMPLONG SAMPANG - Ahmad Khoiri; Mulyadi Mulyadi; Triyo Supriyatno (re-JIEM (Research Journal of Islamic Education Management), 2020)
This study aims to describe the strategy of the madrasa head in implementing the memorizing (tahfidz) al-Qur'an program in MAN 1 Sampang and MA Al-Ittihad Al-Islami Camplong, with sub foci including (1) madrasa head planning, (2) madrasa head program implementation, and (3) the implications of the madrasa head strategy, which was carried out by MAN 1 Sampang and MA Al-Ittihad Al-Islami Camplong Sampang Madura. The results of this study indicate that: 1) planning the tahfidzul Qur'an program namely; cooperating with various parties both inside and outside the school, determining the coach of tahfidz who already memorized 30 juices. 2) The process of implementing the Tahfidz program is carried out every week at 06: 50-07: 30 WIB in each class using the Muroja'ah and Tikrar methods, the depositing process can be carried out on male or female coaches or assistant coaches. 3) Implications of the program of tahfidz al-Qur'an namely; improve the quality of madrasas, the number of student memorization that exceeds the target, and student achievement in non-academic fields. Keyword: Strategy, Remembering, Memorizing, Tikrar